GEOTOURIST POTENTIAL OF POST-MINING REGIONS IN POLAND - NITA, JERZY; MYGA-PIĄTEK, URSZULA (Bulletin of Geography. Physical Geography Series, 2015)
The current article will attempt to confirm that Polish post-mining areas are characterized by high cognitive and aesthetic values and that they have great geotourism potential, which has been little used so far. Tourism is regarded to be one of the most dynamically growing sectors of the global economy and is a phenomenon that occurs in the landscapes of all ecological and altitudinal zones. Geotourism is among the relatively recent types of tourism. Poland is a highly attractive country for geotourism. The aim of this article is to analyze the distribution and size of post-mining areas in Poland and, based on these analyses, to assess the geotourist potential of selected post-mining regions. Based on the distribution of natural resource mining sites and their potential and actual use in geotourism, the authors selected 20 actual and potential geotourist regions in Poland. These regions were divided into three basic categories based on their attractiveness.